Impact of middle level eye care personnel on the delivery of eye care services in South-western Nigeria - Bogunjoko, Tayo J.; Hassan, Adekunle O.; Okonkwo, Ogugua; Akanbi, Toyin; Ulaikere, Mildred; Akinye, Ayodele; Bogunjoko, Halima; Lawal-Sebioniga, Monsurat Y. (International Journal Of Community Medicine And Public Health, 2018)
Background: The objectives of the study were to review the training and assess the impact of middle level eye care personnel (community ophthalmic technician) with skills to complement the services of the ophthalmologist for efficient eye care system and fulfilling vision 2020 goals. Methods: The collaboration between 2010 and 2015 was reviewed with an institutional questionnaire for both Eye Foundation Centre and College of Health Technology in Ijebu, Nigeria: structure of 2 year training Programme and one year internship, community ophthalmic technicians (COT) as assistants to ophthalmologists, hierarchy/career options and challenges and ensuring clinical quality and their strength in the Eye Foundation Eye Health System were appraised. Results: From 2010 to 2015, a total of 72 COTs have graduated, 41(57%) of them employed by the Eye Foundation Hospital Group. Apart from this, 28 did their internship in 2015, 19 (68%) out of this at Eye Foundation establishments in southwestern and north central Nigeria. Others are employed by other government or nongovernmental agencies. From 2010 to 2015, outpatients’ visits have increased from 42,962 to 104,239 at its peak, surgical volume from 3,999 to 18,350 at the Eye Foundation Hospital Group. The COT programme has been accredited by International Joint Commission on Allied health personnel in Ophthalmology (IJCAHPO). Conclusions: COTs with skills are required in large numbers to complement the services of ophthalmologists for efficient eye health system. Their contribution is very important to meet the vision 2020 human resources objectives for Sub-Saharan Africa.